Dancing with ignorance : Utilizing social media to enhance public authorities’ sensemaking abilities in times of crises - Jalonen, Harri; Rantamäki, Aino (IKAM - Institute of Knowledge Asset Management, 2024)
This paper builds on the relatively underexplored yet increasingly intriguing domain of ignorance, a topic that is garnering interest within the academic community. Traditional crisis management often relies on existing knowledge, creating a restricted view of crisis nature and organizational reality. This approach can miss insights from recognizing and understanding the unknown. This paper employs a mixed-methods approach comprising a literature review, interviews, and a Security Café workshop to examine social media’s role in sensemaking in different crisis stages (anticipating, responding, and recovering). The paper’s findings highlight two main contributions: First, it redefines ignorance not just as a void of information but as a pivotal element affecting decision-making during crises. Strategic use of social media is presented as a means for public authorities to manage ignorance by improving their sensemaking processes. This involves the active gathering, verification, and dissemination of information, utilizing social media as a tool for early warning and analysing public sentiment. Second, the paper illustrates how social media serves as a dynamic platform for building trust, fostering public engagement, and combating misinformation before, during, and after a crisis, thereby enhancing public authorities’ capacity to respond to rapidly evolving situations. The paper concludes by advocating a proactive stance in managing ignorance through social media, emphasizing the importance of strategic communication planning, fostering public trust, and collaborative knowledge creation to anticipate and respond to crises effectively.
Keywords: Ignorance; Knowledge formation; social media; crisis management; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|